Penerapan Model Problem Based Learning Berbantuan Role Playing Untuk Meningkatkan Motivasi Belajar Peserta Didik Kelas VII B SMP Negeri 6 Trenggalek Pada Materi Ekologi - Tiara, Rona; Cholifah, Umayatin; Munfaridah, Nuril (Universitas Muslim Buton, 2023)
This study aims to increase the learning motivation of class VII B students of SMP Negeri 6 Trenggalek Semester II for the 2022/2023 Academic Year with the Problem Based Learning model assisted by Role Playing on Ecology material. This research is a Classroom Action Research (CAR) in 2 cycles. The instruments used in this study were questionnaires to measure learning motivation and test questions to measure student learning outcomes. The data analysis technique used in this study is a comparative descriptive technique. The results of this study indicate that: 1) by applying the Problem Based Learning model assisted by Role Playing, students' learning motivation increases; 2) Likewise, the Problem Based Learning model assisted by Role Playing effectively improves student learning outcomes from cycle I to cycle II.